Islamic Ethical Pedagogy for Artificial Intelligence Use: Insights from Islamic Religious Education Teachers in Indonesia - Wahyu Muhammad Ibrohim; Abdul Aziz; Jamali Sahrodi (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study investigates how Islamic Religious Education teachers cultivate ethical use of Artificial Intelligence (AI) in Indonesian Islamic schools amid rapid digital transformation. A qualitative case study was conducted at SMPS IT Nurul Wahdah Pontianak, Indonesia. Data were collected through classroom observations, semi-structured interviews with Islamic Religious Education teachers and school stakeholders, and document analysis. The data were analyzed using an interactive thematic approach involving data reduction, data display, and conclusion drawing, while credibility was ensured through source and method triangulation. The findings reveal that students widely utilize AI for learning, yet its use raises ethical concerns, including overdependence, declining academic integrity, limited critical reflection, and inadequate information verification. In response, teachers implement an integrated pedagogical approach by embedding the Islamic values of ṣidq (truthfulness), amānah (trustworthiness), mas'ūliyyah (responsibility), and tabayyun (critical verification), modelling ethical AI practices, promoting reflective Islamic digital literacy, and strengthening collaboration among schools and families. This study introduces Islamic Ethical Pedagogy as an integrated framework linking AI literacy, ethical governance, teacher agency, and Islamic educational values. The proposed framework provides theoretical and practical guidance for integrating AI responsibly while fostering students' ethical awareness, academic integrity, critical thinking, and character formation in Islamic education.